THE EFFECT OF RETURN ON ASSETS AND RETURN ON EQUITY TO WORKING CAPITAL AT PT. ADARO ENERGY TBK - Rahmi Aminus; M. Adi Renaldi; Faridatul Munawaruh (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
This study aims to determine the effect of the variable Return On Assets and Return On Equity partially and simultaneously on working capital at PT Adaro Energy Tbk. The object of this research is one of the companies engaged in the mining sector based in Indonesia which has started operating since 2005, namely PT Adaro Energy Tbk. The data analysis technique used multiple linear regression analysis and classical assumption test. The results of the study partially show that Return On Assets has a positive effect on working capital, Return On Equity has no effect on working capital while simultaneously Return On Assets and Return On Equity affect working capital at PT Adaro Energy Tbk.